Secure mobile agents for efficient medical information retrieval: A verifiable variable threshold secret sharing approach - Pradeep Kumar; Sur Singh Rawat; Kakoli Banerjee; Ayodeji Olalekan Salau; Gyanendra Kumar; Niraj Singhal (PLoS ONE, 2025)
Mobile Agents are a new type of computing that is replacing the client-server approach. Mobile agents are little pieces of code that function automatically on behalf of the owner. Many applications, such as e-commerce, parallel computing, network management, and health care, use mobile agents. The healthcare industry is one of the most growing fields in any country. As the population increases day by day the requirement of medical resources is proportionally increasing. Due to high patient demand and a severe lack of medical resources, a remote medical healthcare system is required. However, the deployment of remote healthcare systems over the Internet introduces a new set of challenges, including interoperability among heterogeneous networks and the need to navigate through multiple public systems dispersed over insecure networks. This paper explores how mobile agents can effectively tackle these challenges, especially in heterogeneous and potentially malicious environments. A key focus of this research is the development of a mathematical model for secure medical information retrieval. This model incorporates a variable threshold secret-sharing mechanism, employing the Chinese remainder theorem and multiplicative inverse with modular arithmetic at different levels. By integrating these cryptographic techniques, the proposed approach ensures the confidentiality and integrity of medical information during its retrieval, contributing to the overall safety and robustness of mobile agent computing in healthcare scenarios.